2017
DOI: 10.1111/joor.12509
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of adjunctive interventions for accelerating orthodontic tooth movement: a systematic review of systematic reviews

Abstract: This study was aimed to summarise published systematic reviews (SRs) that assess the effects of adjunctive interventions on the acceleration of orthodontic tooth movement (OTM). Electronic and manual searches were performed up to August 2016. Systematic reviews investigating the impact of adjunctive techniques on the promotion of OTM were included. The methodological quality of the included reviews was evaluated using the A Measurement Tool to Assess Systematic Reviews (AMSTAR) scale. The quality of evidence f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 30 publications
2
33
0
1
Order By: Relevance
“…4,10,[25][26][27] Injections were delivered every 3 weeks and repeated until the sixth week following the protocol reported by Rashid et al 5 Although the study continued for 4 months, injections were not continued through the whole duration of the study in order to determine whether PRP injections were enough in the initial phases of tooth movement only, as compared with corticotomy 12 or low-level laser therapy applications. 3 The results of the current study showed a faster rate of canine retraction on the intervention side in the first month by 15% and in the second month by 5%. Despite this increase being statistically significant in the first month (P ¼ .049) and nonsignificant in the second month (P ¼ .772), the results reflected a positive correlation between PRP injection and acceleration of orthodontic tooth movement.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…4,10,[25][26][27] Injections were delivered every 3 weeks and repeated until the sixth week following the protocol reported by Rashid et al 5 Although the study continued for 4 months, injections were not continued through the whole duration of the study in order to determine whether PRP injections were enough in the initial phases of tooth movement only, as compared with corticotomy 12 or low-level laser therapy applications. 3 The results of the current study showed a faster rate of canine retraction on the intervention side in the first month by 15% and in the second month by 5%. Despite this increase being statistically significant in the first month (P ¼ .049) and nonsignificant in the second month (P ¼ .772), the results reflected a positive correlation between PRP injection and acceleration of orthodontic tooth movement.…”
Section: Discussionsupporting
confidence: 48%
“…Although each approach has claimed to be superior to the others in different studies, conflicting evidence concerning each technique still exists. 2,3 Pharmacologic approaches to accelerate the rate of orthodontic tooth movement have been investigated in humans since the 1980s. 4 If proven clinically efficient, pharmacologic approaches might surpass other approaches as they are less invasive, less costly, and more controlled.…”
Section: Introductionmentioning
confidence: 99%
“…Finding the latter would be of great importance to determine future clinical guidelines. Before drawing conclusions for orthodontic clinics, highquality trials are required to conclude about the long-term effects of LLLT and to give the optimal protocols [36]. …”
Section: Resultsmentioning
confidence: 99%
“…The post-extraction sockets 18,19 (even if a first intention closure is performed), periodontal surgery and implantology 20 , orthodontics 21,22 , temporomandibular joints disorders, and neurological conditions may all benefit from superficial irradiation in which part of the laser beam penetrates a deeper level 23,24 .…”
Section: Discussionmentioning
confidence: 99%